PELATIHAN BAHASA INGGRIS PRAKTIS BAGI IBU-IBU PKK DALAM MENGANTISIPASI MELONJAKNYA KEDATANGAN TURIS DI KOTA TOMOHON - Jenie Posumah; Veronika F L Damopolii (ABDIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
Today,English is very urgently useful for all countries, so this is a good time to increase in any parts of humans’, such as education, economy,social,culture,industry,etc,and all of those parts must be supported as soon as possible.It is because global market for all fields are really available now.It must be moved rapidly.One aspect which has the role in increasing English is tourism.Even now, tourism is shaken by pandemic of covid-19 happened at the end of 2019 and run quickly in the early of 2020 (especially in Indonesia), but after about one year later, the government tried to overcome the situation, so at the early of 2021, tourism sector run slowly and slowly wake up toward to any features related to tourism by still applied the health protocol.            One effort to increase the government income, from the upper authority up to the lower authority,by preparation many tour guides who have very important role because there are many interesting ( tourism) places opened,both private and public sectors.These are really interesting things to gain many tourists to visit them.Day by day, there is a significant increasing in tourism sector and it needs to prepare so many tour guides to welcome the tourists.To overcome this situation, it must be available of local citizens as the human’s resources to master English. Short English course for the women covered as PKK group in Kolongan country, Tomohon District is a good way also to anticipate this one.            The short practical English course used the methods such as, explanation, discuss, question and answer,and direct practice of English, so the members could be increased their capability both in theory and especially in practice (more focus on speaking skill).This course aimed to support learning Englih materials effectively.Also, this activity as an applied activity for society at Kolongan country, Tomohon District could run well whenever and wherever they are.